Metabolic characterization of plasma samples in HIV-1-infected individuals. (July 2018) - Zhang, Ting; Sun, Jianping; Du, Haiwei; Su, Haoxiang; Zhang, Yonghong; Jin, Qi
Aim: To identify potential biomarkers for the diagnosis and monitoring of HIV-1 progression.Methods: 19 subjects, diagnosed with HIV-1 infection in the follow-up, prospective, clinical cohort more than 6000 subjects from 2006, were incorporated into our study. The subjects included ten non-progressors and nine rapid progressors. The plasmas of subjects before HIV-1 seroconversion and after seroconversion were collected and analyzed with nontargeted metabolomics.Results: 20:0-Glc-Campesterol and A-norgorgostanol could significantly distinguished after HIV-1 seroconversion from before HIV-1 seroconversion. PG(O-18:0/18:0) could totally distinguish the plasma of rapid progressor before seroconversion from that of nonprogressor before seroconversion.Conclusion: 20:0-Glc-Campesterol, A-norgorgostanol and  PG(O-18:0/18:0) could be potential biomarkers for the diagnosis and monitoring of HIV-1 progression.